Genome Engineering in Plant Using an Efficient CRISPR-xCas9 Toolset With an Expanded PAM Compatibility - Zhang, Chengwei; Kang, Guiting; Liu, Xinxiang; Zhao, Si; Yuan, Shuang; Li, Lu; Yang, Yongxing; Wang, Feipeng; Zhang, Xiang; Yang, Jinxiao (Frontiers in Genome Editing, 2020)
The CRISPR-Cas9 system enables simple, rapid, and effective genome editing in many species. Nevertheless, the requirement of an NGG protospacer adjacent motif (PAM) for the widely used canonical Streptococcus pyogenes Cas9 (SpCas9) limits the potential target sites. The xCas9, an engineered SpCas9 variant, was developed to broaden the PAM compatibility to NG, GAA, and GAT PAMs in human cells. However, no knockout rice plants were generated for GAA PAM sites, and only one edited target with a GAT PAM was reported. In this study, we used tRNA and enhanced sgRNA (esgRNA) to develop an efficient CRISPR-xCas9 genome editing system able to mutate genes at NG, GAA, GAT, and even GAG PAM sites in rice. We also developed the corresponding xCas9-based cytosine base editor (CBE) that can edit the NG and GA PAM sites. These new editing tools will be useful for future rice research or breeding, and may also be applicable for other related plant species.